Strategies to Maintain Water Resources for Sustainability in the Sumbagut Region - Sandy Pradana; Aulya Apta Nienda; Syafrianto Sitanggang; Bram Harya Prima; Glowinner Sihombing; Fernando Depari; Riyadiyanto (Prospect Publishing, 2023)
This study uses a combined approach between economic analysis and observation by Pertamina Regional Sumbagut. The data obtained are analyzed to identify strategies that have been implemented and measure their impact on the sustainability of water resources. The results showed that Pertamina Regional Sumbagut has adopted several important strategies in safeguarding water resources. This strategy includes the use of water-saving technologies in their operations, such as the use of rainwater utilization systems and the use of water-saving methods in production facilities. In addition, Pertamina is also active in monitoring and managing the impact of their operations on water quality. The implementation of these strategies has had a positive impact in safeguarding water resources for sustainability. Pertamina Regional Sumbagut has succeeded in reducing water consumption, making savings in water consumption costs, and minimizing negative impacts on water quality in the region. The study provides valuable insights for Pertamina Regional Sumbagut and other energy companies in sustainable water management. It is hoped that the results of this study can encourage further efforts to continue to improve water saving practices.